RISK-REWARD TRADEOFF AND BEHAVIOR OF ISLAMIC AND CONVENTIONAL STOCK MARKET INDICES IN BOSNIA AND HERZEGOVINA - Irfan Djedović; Edin Djedović (Economic Review)
This paper empirically examines tradeoff between risk and return for the Islamic stock market index in Bosnia and Herzegovina (BiH) (SASXBBI) and compares it with risk-return tradeoff of the conventional stock market index in BiH (SASX-30). Furthermore, it examines the eventual impact of the conventional stock market index in BiH on the SASXBBI. The study used daily index observations spanning in the period from October 2016 until December 2018. The data were obtained from the Sarajevo Stock Exchange database. The risk-reward ratio is used to investigate the tradeoff between risk and return of the indices, while Ordinary Least Squares (OLS) regression analysis is used to investigate the impact. The results show that there is better risk-reward tradeoff in the conventional index in BiH compared to the Islamic index in BiH. Also, the results suggest that conventional index return has a significant positive impact on Islamic index return in BiH